The Effect of Liquid Organic Fertilizer from Fish Waste and Trichokompos on The Growth of Soybean Plants (Glycine max) of The Edamame Variety - Aprilia, Nanda; Rambe, Rahmi Dwi Handayani; Gunawan, Indra (PT Inovasi Pratama Internasional, 2025)
Soybeans (Glycine max) are the third most important food commodity after rice and corn and are one of the legumes used as a major source of protein and vegetable oil in the world. This study was conducted at the Experimental Farm of the Faculty of Agriculture, University of Islam Sumatra Utara, at an elevation of approximately 25 meters above sea level. This study aims to determine the effect of liquid organic fertilizer from fish waste and Trichokompos on the growth of Edamame soybean plants. This study employs a factorial randomized block design (RBD), with the first factor being Fish Waste Liquid Organic Fertilizer, consisting of four levels: L0 = No Fish Waste Liquid Organic Fertilizer (control), L1 = Fish Waste Liquid Organic Fertilizer 100 ml/polybag, L2 = 200 ml of liquid organic fertilizer from fish waste per polybag, L3 = 300 ml of liquid organic fertilizer from fish waste per polybag. The second factor was Trichokompos fertilizer, consisting of 4 levels: T0 = No Trichokompos fertilizer (control), T1 = Trichokompos fertilizer 12.5 tons/ha (62.5 g/polybag), T2 = Trichokompos fertilizer 25 tons/ha (125 g/polybag), T3 = Trichokompos fertilizer 37.5 tons/ha (187.5 g/polybag). The results of the study indicate that the application of Fish Waste Liquid Organic Fertilizer affects plant height, number of leaves, and stem diameter. Trichokompos affects plant height but does not affect the number of branches or stem diameter. The interaction between Fish Waste Liquid Organic Fertilizer and Trichokompos did not affect any of the observed parameters.